Competition and regulation in a differentiated good market - Raffaele Fiocco (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
This paper addresses the issue of how to design the institutional structure of an industry which provides two differentiated products. One good is supplied by a regulated monopoly and the other is produced in a competitive (unregulated) segment. Two possible institutional patterns are compared. Under 'concentration' the regulated firm can enter the competitive segment by owning one firm which operates there (even though the two firms must be legally unbundled). The regime of 'separation' implies that regulated activities are totally unbundled from the unregulated ones, that is, common ownership is not allowed. When the regulator does not know the regulated monopoly's cost of production, we find that the pattern of separation improves (expected) social welfare as long as goods are substitutes. Conversely, concentration performs better in case of complementarity.
Keywords: D82; L11; L51; 330; competition; complementarity; concentration; regulation; separation; substitutability; Regulierung; Produktdifferenzierung; Unternehmensregulierung; Wettbewerb; Wirtschaftskonzentration; Theorie